Vibraciones elásticas en presencia de una serie de dislocaciones de tornillo - Aya Baquero, Hugo; Gachevski, Valeri (Ingeniería, 2001)
Elastic tensions resulting from a dislocation array are significantly higher than those from an isolated dislocation. Therefore their influence on elástic vibrations is higher too. In this paper elastic vibration spectra in elastic field yielded by an infinite array of screw dislocations was analyzed and compared with the spectra of vibrations in the elástic field of an isolated screw dislocation.